Presence and severity of esophageal varices drives portal hypertension-related complications in compensated advanced nonalcoholic fatty liver disease. (March 2023) - Pennisi, G.; Enea, M.; Viganò, M.; Schepis, F.; de Ledinghen, V.; Berzigotti, A.; Wong, V.; Fracanzani, A.L.; Sebastiani, G.; Romero-Gomez, M.; Bugianesi, E.; Svegliati-Baroni, G.; et al.
Abstract : Background/Aim: We aimed to evaluate the impact of esophageal varices(EV) and their changes during follow-up on the risk of developing liver events in patients with compensated advanced chronic liver disease(cACLD) due to NAFLD. We also assessed diagnostic accuracy of noninvasive scores for predicting the development of liver events and for identifying patients at low risk of high-risk EV. Materials/Methods: We assessed 629 patients with NAFLD-related cACLD who had baseline and follow-up esophagogastroduodenoscopy(EGD), and clinical follow-up to record decompensation, portal vein thrombosis(PVT) and hepatocellular carcinoma. Results: Small and large EV were observed at baseline in 30% and 15.9% of patients, respectively. The 4-year rate of EV development from absence at baseline, and of progression from small to large EV were 16.3% and 22.4%, respectively. Presence of diabetes and ≥5% increase in BMI were associated with worsening of EV status. At multivariate Cox regression analysis, small(HR 2.24, 95%C.I. 1.47-3.41) and large (HR 3.86, 95%C.I. 2.34-6.39) EV were independently associated with decompensation. When considering EV status and EV trajectories, baseline and/or follow-up small EV(HR 2.65, 95%C.I. 1.39-5.05), and baseline and/or follow-up large EV(HR 4.90, 95%C.I. 2.49-9.63) were independently associated with decompensation as compared to baseline and/or follow-up absence of EV. Presence of small(HR 2.8 (95%C.I.1.16-6.74) and large(HR 5.29, 95%C.I. 1.96-14.2) EV were also independently associated with PVT occurrence. Conclusion: In NAFLD-related cACLD, the presence, severity and evolution of EV well stratify the risk of developing decompensation and PVT.